Impact of medication characteristics and adverse drug events on hospital admission after an emergency department visit: Prospective cohort study. Issue 7 (23rd April 2021) - Lohan, Laura; Marin, Gregory; Faucanie, Marie; Laureau, Marion; Macioce, Valérie; Perier, Damien; Pinzani, Veronique; Giraud, Isabelle; Castet‐Nicolas, Audrey; Jalabert, Anne; Villiet, Maxime; Sebbane, Mustapha; et al.
Abstract: Objectives: Emergency department (ED) overcrowding is a problem for the delivery of adequate and timely emergency care. To improve patient flow and the admission process, the quick prediction of a patient's need for admission is crucial. We aimed to investigate the variables associated with hospitalisation after an ED visit, with a particular focus on the variables related to medication. Methods: This prospective study was conducted from 2011 to 2018 in subacute medical ED of a French University Hospital. Specialised EDs (paediatric, gynaecologic, head and neck and psychiatric) and the outpatient unit of the ED were not included. Participation in this study was proposed to all adult patients who underwent a medication history interview with a pharmacist. Pharmacists conducted structured interviews for the completion of the medication history and the detection of adverse drug events (ADE). Relations between patient characteristics and hospitalisation were analysed using logistic regression. Results: Among the 14 511 included patients, 5972 (41.2%) were hospitalised including 69 deaths. In total, 7458 patients (51.4%) took more than 5 medications and 2846 patients (19.6%) had an ADE detected during the ED visit. In hospitalised patients, bleeding (32.2%) and metabolic disorders (16.8%) were the most observed ADE symptoms. Variables associated with increased hospital admission included 2 demographic variables (age, male gender), 4 clinical variables (renal and hepatic failures, alcohol addiction, ED visit for respiratory reason) and 6 medication‐related variables (medications >5, use of blood, systemic anti‐infective, metabolism and antineoplastic/immunomodulating medications and ADE). Conclusion: We identified variables associated with hospitalisation including drug‐related variables. These results point out the importance and the relevance of collecting medication data in a subacute medical ED (study registered on ClinicalTrials.gov, NCT03442010).